THE IMPORTANCE AND PERFORMANCE ANALYSIS OF SERVICE QUALITY AT GARDENIA COUNTRY INN TOMOHON - Senduk, Nasrani Janet; Tielung, Maria V. J. (FEB Universitas Sam Ratulangi Manado, 2016)
Abstract: In the highly competitive of hospitality industry, service becomes one of the most important things for gaining sustainable competitive advantages in the marketplace. Service quality is a focused evaluation that reflects the customer?s perception of specific dimensions of service: reliability, responsiveness, assurance and empathy and tangibles. The objective of this research is to know the importance and performance of service quality at Gardenia Country Inn Tomohon by using an Importance and Performance Analysis (IPA). The sample of this research is 50 respondents which is the customer of Gardenia Country Inn Tomohon. The key result were the importance of service quality in Gardenia Country Inn Tomohon is the services considered extremely important to the customers and the performance of Gardenia Country Inn Tomohon mostly has good performances so Gardenia Country Inn just to keep up the good work and keep maintenance their service quality to keep the customer satisfaction. Keywords: Service Quality, Importance Performance Analysis, Hospitality Industry